Warfarin Use Is Associated with Increased Mortality at One Year in Patients with Idiopathic Pulmonary Fibrosis - Syeda Fatima Naqvi; Amir Humza Sohail; Dhairya A. Lakhani; James Maurer; Sarah Sofka; Yousaf B. Hadi (Pulmonary Medicine)
Rationale. Previous data suggest that warfarin may worsen outcomes in IPF in patients with no indication for anticoagulation when compared to placebo. However, warfarin continues to be widely used for cardiac and thromboembolic indications in this patient population due to unavailability of data comparing warfarin with other anticoagulants in patients with IPF. Objectives. We studied the safety and efficacy of warfarin compared to direct acting oral anticoagulant use in patients with IPF. Methods. We conducted a retrospective cohort study of all patients with IPF who were prescribed warfarin or direct acting oral anticoagulants (DOACs) for cardiac or thromboembolic indications and followed at our institute for their care. Univariate tests and multivariable logistic regression analyses were used for assessing association of variables with outcomes. Results. A total of 73 patients were included in the study with 28 and 45 patients in the warfarin and DOAC groups, respectively. Univariable analysis revealed a significant difference in mortality in one year between warfarin and DOAC groups (7/28 vs. 3/45, p value 0.027). Significantly more patients in the warfarin group suffered an exacerbation that required hospitalization within one year (9/28 vs. 5/45, p value 0.026). Multivariate logistic regression analysis showed that anticoagulation with warfarin was independently associated with mortality at one-year follow-up (OR: 77.4, 95% CI: 5.94–409.3, p value: 0.007). Conclusion. In our study of patients with IPF requiring anticoagulants, we noted statistically significant higher mortality with warfarin anticoagulation when compared to DOAC use. Further larger prospective studies are needed to confirm these findings.